The virulence factor urease and its unexplored role in the metabolism of Cryptococcus neoformans. Issue 4 (3rd June 2020) - Toplis, Barbra; Bosch, Caylin; Schwartz, Ilan S; Kenyon, Chris; Boekhout, Teun; Perfect, John R; Botha, Alfred
ABSTRACT: Cryptococcal urease is believed to be important for the degradation of exogenous urea that the yeast encounters both in its natural environment and within the human host. Endogenous urea produced by the yeast's own metabolic reactions, however, may also serve as a substrate for the urease enzyme. Using wild-type, urease-deletion mutant and urease-reconstituted strains of Cryptococcus neoformans H99, we studied reactions located up- and downstream from endogenous urea. We demonstrated that urease is important for cryptococcal growth and that, compared to nutrient-rich conditions at 26°C, urease activity is higher under nutrient-limited conditions at 37°C. Compared to cells with a functional urease enzyme, urease-deficient cells had significantly higher intracellular urea levels and also showed more arginase activity, which may act as a potential source of endogenous urea. Metabolic reactions linked to arginase were also affected, since urease-positive and urease-negative cells differed with respect to agmatinase activity, polyamine synthesis, and intracellular levels of proline and reactive oxygen species. Lastly, urease-deficient cells showed higher melanin levels at 26°C than wild-type cells, while the inverse was observed at 37°C. These results suggest that cryptococcal urease is associated with the functioning of key metabolic pathways within the yeast cell. Abstract : The urease enzyme, a major virulence factor of Cryptococcus neoformans, is linked to several key metabolic pathways within the yeast cell.